(In)justice in modelled climate futures: A review of integrated assessment modelling critiques through a justice lens. (October 2022) - Rubiano Rivadeneira, Natalia; Carton, Wim
Abstract: Integrated Assessment Models (IAMs) have become the dominant approach for envisioning different mitigation scenarios. While they are not intended to deal with justice, IAM assumptions and structure have justice implications that have not been explicitly discussed or clearly elucidated in critical accounts of modelling practices. Given their key influence in policy decisions and the increasing imperative for just transitions and climate action, a more explicit consideration of the justice dimensions of IAM-derived mitigation pathways is necessary. This paper reviews existing critiques to IAMs through a three-dimensional justice lens to examine the extent to which justice concerns emerge or remain unnoticed in the literature. This review helps substantiate how disciplinary and geographical assumptions and norms shape policy choices. Focusing mostly on the role of technoeconomic framings and processes of model-based knowledge production, and drawing from critical justice theorists, such as Nancy Fraser, the article shows how dominant approaches to justice have overlooked questions of recognition and their subsuming distributional and participational concerns. It also points to the need to engage with other knowledge systems and approaches through cognitive justice, for a more transformative critique of policy relevant climate knowledge, as well as to strive for more diverse, equitable and inclusive policy options.